Ice-flow modeling results to assist the interpretation of millennial-scale ice cores recovered at the high-Alpine ice drilling site Colle Gnifetti, Swiss/Italian Alps - Licciulli, Carlo; Bohleber, Pascal; Lier, Josef; Gagliardini, Olivier; Hölzle, Martin; Eisen, Olaf (PANGAEA - Publishing Network for Geoscientific and Environmental Data, 2019)
Licciulli, Carlo; Bohleber, Pascal; Lier, Josef; Gagliardini, Olivier; Hoelzle, Martin; Eisen, Olaf (2019): Ice-flow modeling results to assist the interpretation of millennial-scale ice cores recovered at the high-Alpine ice drilling site Colle Gnifetti, Swiss/Italian Alps. PANGAEA, https://doi.org/10.1594/PANGAEA.906016, Supplement to: Licciulli, C et al. (2019): A full Stokes ice-flow model to assist the interpretation of millennial-scale ice cores at the high-Alpine drilling site Colle Gnifetti, Swiss/Italian Alps. Journal of Glaciology, 1-14, https://doi.org/10.1017/jog.2019.82